2012
DOI: 10.4028/www.scientific.net/msf.730-732.975
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Mono-Substituted Borotungstate: Characterization and Catalytic Application

Abstract: The Keggin-type TBA4H2[BW11Mn(H2O)O39].H2O (BW11Mn) compound was isolated and characterized. The first sphere of coordination for the manganese atom was determined by EXAFS analysis. Six oxygen atoms were found in the range of 1.80-2.64 Å from the manganese. BW11Mn showed to be an active, efficient and selective catalyst for cis-cyclooctene (1a) epoxidation in the presence of stoichiometric quantities of H2O2. After 5 h of reaction almost complete conversion was achieved (86% of conversion). Selectivity was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…48 The obtained compound was characterized by elemental analysis (C, H, N, W, Mn), thermogravimetry and infrared spectroscopy and the results were in agreement with those previously published. 47,48…”
Section: Reagents and Synthetic Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…48 The obtained compound was characterized by elemental analysis (C, H, N, W, Mn), thermogravimetry and infrared spectroscopy and the results were in agreement with those previously published. 47,48…”
Section: Reagents and Synthetic Proceduresmentioning
confidence: 99%
“…7,9,14,18,19 Among others, the catalytic efficiency of lacunary and transition metal-substituted Keggin-type polyoxotungstates in the oxidation of S-compounds has already been demonstrated in several reports. 27,[37][38][39][40][41][42][43][44][45][46] Our previous experience with the use of the undecatungstoboromanganateIJIII) anion, [BW 11 MnIJH 2 O)O 39 ] 6− (BW 11 Mn), in oxidative catalysis has shown that it is an efficient and robust catalyst for the oxidation with H 2 O 2 of several types of substrates, 28,31,[47][48][49] suggesting that it could be a good candidate to be used for the oxidation of organosulfur compounds. Moreover, our research group has developed a catalytic oxidation system of organosulfur derivatives under mild conditions using metalloporphyrin complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with current drugs, the unique advantage of POMs lies in the fact that the composition, molecular structure and physiochemical properties are adjustable and can be easily synthesized from readily available precursors in a few synthetic steps [8][9][10][11] . More importantly, another advantage of POMs is that transition metals can be introduced into their structure to obtain transition metal-substituted POMs, such as mono, dis or tri-substituted polyanions [12][13][14] . The combination of transition metals and vacancy POMs changed the composition, charge and physicochemical properties of the original saturated POMs, which also showed certain advantages in biological activity [15,16] .…”
Section: Introductionmentioning
confidence: 99%